Logarithm model prediction for 2008 Beijing Olympic Games - Wang, J.; Jiang, Y. (International Journal of Sports Science and Engineering, 2008)
Considering the result of a sport event regarding years as a time serial, it can be described by a model of time serial including certain model and uncertain model. In this test we put forward logarithm model to predict sports results. According to the method provided in this text we carried on "prediction" of man's track events of 2004 Olympic Games and the "prediction" accuracy came to above 97%(average 99.1647%).At last, we built up logarithm model and carry on the error test. The result shows that logarithm model prediction can be believable and can be use to predict sports result.